VET in Schools: The adoption of National Training Packages in a secondary school setting - Dixon, Kathryn; Pelliccione, Lina (Australian Council for Educational Research, 2003)
Growing pressure is being placed on schools as students, employers and government look at the economic, demographic and vocational environments of the present, expecting them to adequately prepare students for an ever widening post-school vocational future. One of the major factors contributing to the lack of adoption of any innovation is the entrenched attitudes of the teaching staff along with an associated reluctance to change. Vocational Education and Training programs, in one form or another, have been circling the change process in Australian schools since 1930 and yet still locatethemselves largely in the adoption and implementation phase rather than becoming institutionalised and embedded in the life of the organisation. It is clear that the way in which teachers construct meaning for innovations is a major factor in whether or not they are institutionalised in schools, however, this paper also investigates the influence of organisational culture, infrastructure, leadership and policy on the adoption of National Training Packages and their components in a Western Australian case study school.